Cyclophosphamide and Mycophenolate Mofetil as Induction Therapy in Lupus Nephritis - Božić Majstorović, Ljubinka; Popović-Pejičić, Snježana; Mrđa, Jelena; Mrđa, Vladimir; Ovčina, Irma (Scripta Medica, 2024)
Background/Aim: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with multisystemic involvement. Almost 50 % of patients who suffer from systemic lupus erythematosus have lupus nephritis (LN) as well. Mycophenolate mofetil (MMF) or intravenous cyclophosphamide (CYC) are recommended as preferred therapy. The aim of this study was to see how MMF and CYC, when compared, are efficient in dealing with LN. Methods: Study included 53 SLE patients with biopsy-proven class III and class IV LN. Twenty-two patients (42 %) were treated with MMF (dosage 2-3 g/day) and 31 patients (58 %) were treated with CYC (0.5 to 1.0 g/m2 in monthly pulses) in a 24-week induction study. Outcome of interest was the improvement in serum creatinine, proteinuria and creatinine clearance. Primary end point included complete renal remission defined as serum creatinine within 25 % of baseline before flare and proteinuria < 0.5 g/24 h. Secondary end point included complete renal remission in follow-up period. Results: The results revealed that response between two groups was not notably different (χ2 = 0.151, p = 0.697). Four out of 22 patients (18.2 %) in MMF group and 7 out of 31 patients (22.6 %) in CYC group had complete renal remission. Most patients from both groups showed improvement from the clinical point of view. Secondary end point was also similar between treatment groups. Conclusion: The study showed same efficiency between these treatment groups, MMF and CYC as induction for LN. No crucial differences were identified between MMF and CYC groups in terms of renal remission.